Epidemiological aspects of uterine myomas among nulligest women at the general reference hospital of Panzi in Democratic Republic of the Congo - Balungwe, Sifa; Maroyi, Raha; Joyeux, Mpakanyi; Omari, Mukango; Philémon, Mulongo; Olivier, Nakiyo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Myomas appear early in young women. The objective of this study was to evaluate the frequency of uterine myomas among nulligest women screened at the Panzi Hospital in South Kivu. Methods: A cross-sectional study was conducted among women aged 20-35 years during the period from 01 August 2018 to 01 August 2019. Women were recruited for screening after their informed consent. Informed consent was sought prior to participation in the study. The main data collection tools were the survey questionnaire. An individual survey questionnaire was used for data collection, laboratory records and trans-abdominal ultrasound. Descriptive statistics were calculated. Results: The median age of the women was 25 years. Positive myotomy was noted in 45.9% of cases. Submucosal and subperitoneal localization was predominant (48.6%). Young, unmarried, overweight women were the most common. The mean age of the menarche was 11.83±1.48 years. The consumption of red meat, green vegetables and alcohol was more noted. Exposure to the sun and wearing half-covered clothing were also noted. Abdominal and lumbar pain were the main symptoms observed. The majority used lightening products. Conclusions: The study notes the early appearance of uterine myomas among women aged 20-35 years in our environment. A mass evaluation and screening of this population is necessary to establish prevention and the best management.